2008
DOI: 10.1101/gad.1673408
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ERAD and ER stress are early and specific events in polyglutamine toxicity

Abstract: Protein misfolding, whether caused by aging, environmental factors, or genetic mutations, is a common basis for neurodegenerative diseases. The misfolding of proteins with abnormally long polyglutamine (polyQ) expansions causes several neurodegenerative disorders, such as Huntington's disease (HD). Although many cellular pathways have been documented to be impaired in HD, the primary triggers of polyQ toxicity remain elusive. We report that yeast cells and neuron-like PC12 cells expressing polyQ-expanded hunti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
296
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(317 citation statements)
references
References 57 publications
15
296
0
Order By: Relevance
“…involved in the degradation of mutant neuroserpin strongly suggests that VCP/p97 cooperates with Hrd1 and gp78 for neuroserpin degradation. The N-terminal fragments of polyQ-expanded huntingtin (Nhtt) and ataxin-3 inhibit the function of ERAD and retrotranslocation (33,34). In our observations, we also found that the polyQ-expanded Nhtt or ataxin-3 significantly stimulates mutant neuroserpin aggregation and perturbs its proteasomal degradation (data not shown).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…involved in the degradation of mutant neuroserpin strongly suggests that VCP/p97 cooperates with Hrd1 and gp78 for neuroserpin degradation. The N-terminal fragments of polyQ-expanded huntingtin (Nhtt) and ataxin-3 inhibit the function of ERAD and retrotranslocation (33,34). In our observations, we also found that the polyQ-expanded Nhtt or ataxin-3 significantly stimulates mutant neuroserpin aggregation and perturbs its proteasomal degradation (data not shown).…”
Section: Discussionsupporting
confidence: 70%
“…In our observations, we also found that the polyQ-expanded Nhtt or ataxin-3 significantly stimulates mutant neuroserpin aggregation and perturbs its proteasomal degradation (data not shown). As the polyQexpanded Nhtt and ataxin-3 affect ERAD by influencing the VCP complex (33,34), and VCP deficiency significantly decreases mutant neuroserpin degradation rates (Fig. 2D), these data further suggest that the ERAD machinery is involved in mutant neuroserpin degradation.…”
Section: Discussionmentioning
confidence: 55%
“…Precedent for such a connection has been established previously. For example, HSP70 inhibition might lead to the formation of cytosolic aggregates, and previous work demonstrated that poly-glutamine aggregates directly interfere with components of the ER-associated degradation (ERAD) pathway, which in turn induces the UPR (42). We also showed previously that perturbing cytosolic HSP70 disables ERAD and triggers the UPR, particularly when membrane-integrated, misfolded ER proteins must be cleared (43).…”
Section: Discussionmentioning
confidence: 97%
“…The role of the UPR in the nervous system in physiological or neurodegenerative conditions remains only partially understood and somewhat controversial (for a discussion see [77]), but recent evidence suggests that ER stress is a common neuronal response to injury or neurodegenerative stimuli and that the UPR is a general mechanism in neurodegeneration. Examples for neurodegenerative diseases for which a UPR contribution has been proposed include Parkinson's disease [78], Huntington's disease [79], and AD [80]. More specifically, a role of axonal ER stress or UPR has been is suggested by the finding of elevated ER stress markers within motorneuron axons in a mouse model for ALS [81], and in response to axotomy [82] or ischemic injury [83].…”
Section: Stress Signaling In Axonsmentioning
confidence: 99%